Advances in Transitional Flow Modeling Applications to Helicopter Rotors - Sheng, Chunhua; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book provides a comprehensive description of numerical methods and validation processes for predicting transitional flows based on the Langtry-Menter local correlation-based transition model, integrated with both one-equation Spalart-Allmaras (S-A) and two-equation Shear Stress Transport (SST) turbulence models. A comparative study is presented to combine the respective merits of the two coupling methods in the context of predicting the boundary-layer transition phenomenon from fundamental benchmark flows to realistic helicopter rotors. The book will of interest to industrial practitioners working in aerodynamic design and the analysis of fixed-wing or rotary wing aircraft, while also offering advanced reading material for graduate students in the research areas of Computational Fluid Dynamics (CFD), turbulence modeling and related fields.
Introduction -- Related Works -- Computational Fluid Dynamic Method -- Turbulence Modeling Method -- Validation of Transition Models -- Applications to Helicopter Rotors -- Recommendations.
Keywords: Aerospace engineering; Astronautics; Continuum mechanics; Fluid mechanics; Aerospace Technology and Astronautics; Continuum Mechanics; Engineering Fluid Dynamics